Board Effectiveness and Cost of Debt - Lorca, Carmen; Sánchez-Ballesta, Juan P.; García-Meca, Emma (2011)
Does the board of directors influence cost of debt financing? This study of a sample of Spanish listed companies during the period 2004–2007 provides some evidence about the question. The results suggest that two board attributes – director ownership and board activity – appear to influence in the risk assessment of debtholders because of their ability to reduce agency cost and information asymmetry. We also find a non-linear relationship between board size and cost of debt, suggesting that from certain levels the benefits of large boards may be outweighed by the cost of poorer communication and increased decision-making time.
Keywords: Cost of debt; Corporate Governance; Board of directors